2002
DOI: 10.1080/09637480220138124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors to coronary heart disease in an Arab-American population in Southeast Michigan

Abstract: Although significant advances have been made in the area of cardiovascular disease, few studies have targeted ethnic groups. There is a large and growing Arab-American (AA) population living in Southeast Michigan, whose risk of cardiovascular disease may be on the increase. The objective of this study was to evaluate the prevalence of cardiovascular disease risk factors and associated behavioral factors in an AA community with a large population of emigrants, subjected to significant lifestyle changes. Three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 3 publications
1
34
2
Order By: Relevance
“…To grasp the magnitude of this problem, suffice it to compare our findings (46.3% obesity among women) with estimates from other Mediterranean countries, which share many climatic and nutritional patterns with Syria such as Spain (15.2%), Greece (15%), and Turkey (29.4%) (44)(45)(46). On the other hand, obesity among women of Arab origin in the US is lower than that reported in Aran countries (47), indicating the importance of the local environments. Obesity among women in Syria is likely rooted in the social norms and gender roles of traditional Arab societies, whereby women are mainly looked at as child bearer-rearers.…”
Section: Discussionmentioning
confidence: 89%
“…To grasp the magnitude of this problem, suffice it to compare our findings (46.3% obesity among women) with estimates from other Mediterranean countries, which share many climatic and nutritional patterns with Syria such as Spain (15.2%), Greece (15%), and Turkey (29.4%) (44)(45)(46). On the other hand, obesity among women of Arab origin in the US is lower than that reported in Aran countries (47), indicating the importance of the local environments. Obesity among women in Syria is likely rooted in the social norms and gender roles of traditional Arab societies, whereby women are mainly looked at as child bearer-rearers.…”
Section: Discussionmentioning
confidence: 89%
“…7 The potential role of acculturation (ie, physical inactivity, obesity, stress, consumption of high-fat diets, and smoking) on increasing risks for cardiovascular disease (ie, HTN, coronary artery disease) among Arab Americans living in the United States suggests that HTN may be underreported in this population. 7,8,1214 …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, numerous population-based and intervention studies have identified non-HDL-C as a key risk factor for CHD (9)(10)(11). However, few studies have reported on the correlation between non-HDL-C and CHD in the aged, especially in southwest China.…”
Section: Introductionmentioning
confidence: 99%